Bisphenol A (BPA) as a Contributing Factor to Decreased Fertility in Humans: a Review of the Latest Evidence - Martyna Kania; Agnieszka Adamowska; Alicja Śniatała; Hanna Bartkowiak; Damian Grubski; Kacper Ziarnik; Filip Nadolny; Jędrzej Jabłoński (Journal of Education, Health and Sport)
Introduction Bisphenol A (BPA) is a synthetic compound widely used in producing consumer plastics like polycarbonate and epoxy resins. Recognized as an endocrine-disrupting chemical (EDC), BPA has been linked to various adverse health effects, including impacts on human fertility. Exposure to BPA has been associated with infertility risks not only through direct mechanisms but also by causing transgenerational effects, potentially compromising fertility in future generations.